Investigating The Impact of Tiktok Application Towards Speaking Proficency - Kurnia Sakti; Abdul Rohman; Widi Syahtia Pane (Wadah Inovasi Indonesia, 2023)
Background:Individuals use spoken language when they speak, which is a sort of verbal communication. Speaking is animportant action in which a speaker presents his or her ideas and communicates with the audience. The messagedelivered by words or spoken language that provides meaning is referred to as verbal communication (Krauss,2012). Methodology:According to Creswell (2009:3), the term